Nagging : does it work and what cost? - Chung, Abigail (2019)
This qualitative interview study involving 31 individuals, 22 of which belong to parent-child dyads, investigates the effects of nagging, an understudied form of persuasion used in interpersonal relationships. Guided by the framework of social control theory and psychological reactance, this study found a spectrum of behavioral compliance outcomes, and nagging can both positively and negatively impact relationship quality. This study enables individuals to better weigh the costs and benefits of nagging. Implications for further research are also discussed.